Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Prior Medical Conditions and Medication use and Risk of non-Hodgkin lymphoma in Connecticut United States Women - Yawei Zhang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Lindsay McOmber Morton; Bing Zhang; Kaiyong Zou; Stuart Flynn; Giovanni Tallini; Patricia H. Owens; Tongzhang Zheng (Cancer Causes & Control, 2004)

Invertebrate community sampling of woodland field layers: Trials of two techniques involving enclosures - Colin Moffatt; Stuart McNeill; Alan J. Morton (Journal of Insect Conservation, 2003)

Alcohol use and risk of non-Hodgkin's lymphoma among Connecticut women (United States) - Lindsay McOmber Morton; Theodore R. Holford; Brian Leaderer; Yawei Zhang; Shelia Hoar Zahm; Peter Boyle; Stuart Flynn; Giovanni Tallini; Patricia H. Owens; Bing Zhang; Tongzhang Zheng (Cancer Causes & Control, 2003)